Pengaruh Penerapan Metode Pembelajaran Snowball Throwing Terhadap Peningkatan Prestasi Belajar Matematika Siswa Tunarungu Ditinjau Dari Efikasi Diri Akademik - Lilik Fadlilatin Azizah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
The limited proficiency in deaf students led to difficulty communicating for deaf students that impact on low mathematics achievement. The ability to learn math that requires abstract thinking skills through information received has not been able to be fully achieved, due to limitations in hearing received by the students. This research was conducted as a quasi-experimental. Nine of deaf students at SMPLB Negeri Saronggi aged between 15-18 years who have low math achievement that performed a pre-test with daily test, these students who later became the subject of research. They were given intervention Snowball Throwing learning method for 3 sessions. The learning method is applied for ± 3 hours. 2 weeks after intervention, conducted interviews and post-intervention measurements using daily tests of mathematics. Based on results of hypothesis testing with Wilcoxon analysis obtained value asymp sig = 0 008 <α = 0. 05, that was Ho rejected, which means there is the effect of intervention by snowball throwing learning method significantly to improve mathematics achievement in deaf students before and after treatment. This research proves that the intervention snowball throwing learning methods is considered successful in improving learning achievement with high academic self-efficacy in deaf students of SMPLB Negeri Saronggi. The teacher also said that he obtained new information on new methods of learning and skills in teaching and learning mathematics.